Potentials and Constraints of Using Warehouse Receipts Financing - World Bank Group (World Bank, Washington, DC, 2015)
The paper starts with an overview of Cambodia’s rice sector, with a particular attention to aspects which affect its need for external working capital finance, and characteristics and constraints that could hinder access to such finance (e.g., warehousing capacity, processing constraints, logistics, and market risks). Chapter two describes the general conditions for crop-based financing in Cambodia’s rice sector. Chapter three discusses policy options for enhancing the use of paddy and rice as collateral for financing. The chapter sets out the two main modalities: collateral management, and public warehousing. Both collateral management and public warehousing work best when certain support structures are in place, in particular an indemnity system, a system for the electronic trading of warehouse receipts, and a facility for refinancing warehouse receipt loans (which could be managed by the Central Bank or outsourced to another competent entity such as an investment fund). These are discussed in separate sections. The various sections describe the situation as currently prevails in Cambodia, and provide suggestions on how to move forward, including in terms of possible government supports. Case studies on international experience are used to illustrate options and pitfalls. A final section concludes, with a focus on policy options for the Government of Cambodia and aid donors, the detailed terms of reference for a possible pilot project can be found in annex three.